[PP.22.04] ASSOCIATION BETWEEN PLASMA ALDOSTERONE LEVEL AND ALBUMINURIA IN NEVER TREATED, NON-DIABETIC HYPERTENSIVE PATIENTS. (September 2016) - Catena, C.; Colussi, G.L.; Novello, M.; Brosolo, G.; Bertin, N.; Sechi, L.A.
Abstract : Objective: Animal and clinical studies suggest that inappropriately elevated plasma aldosterone (PA) levels are associated with greater urinary protein excretion. In hypertension, this type of evidence has been obtained in subjects in whom use of antihypertensive drugs or presence of diabetes or severe impairment of renal function were important confounders. Design and method: In this cross-sectional analysis, we included 242 treatment-naive, non-diabetic patients with essential hypertension (age 45 ± 12 years; 133 males) and 24-h creatinine clearance > 30 ml/ min/1.73 m2. In these patients we measured anthropometric and clinical variables, plasma levels of glucose, lipids, insulin, aldosterone, and active renin, and calculated the HOMA-index. Urinary protein losses were assessed as the urinary albumin/urinary creatinine ratio (UAE/UCr) and total 24-h urinary protein excretion (UPE). For statistical purposes patients were divided into quartiles of PA levels. Results: Hypertensive patients with the highest PA levels had significantly higher blood pressure, active renin and both UAE/UCr and UPE than patients with the lowest PA. Univariate correlation analysis indicated that blood pressure and PA levels were significantly and directly related with both UAE/UCr and UPE. No relationships were observed between the glycometabolic or lipid variables and UAE/UCr or UPE. Multivariate regression analysis showed that PA levels were related to higher UAE/UCr and UPE independent of blood pressure and 24-h creatinine clearance. Conclusions: In treatment-naive, non-diabetic hypertensive patients without severe impairment of renal function elevated PA levels might contribute to urinary protein losses independent of blood pressure and other metabolic factors.